Five days exposure to high dietary fat intake has no impact on the performance of a preloaded 5km treadmill based time trial in endurance-trained women - Fletcher, G.; Glover, E. I.; Thompson, J. L.; Wallis, G. A. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
Manipulating the dietary intake of carbohydrate and fat results in differences in the circulating hormonal and metabolic milieu alongside differences in the myocellular substrate storage profile. These divergent profiles can dramatically impact substrate utilisation during exercise, potentially impacting endurance performance. However, at least in men, improvements in endurance performance following a high fat diet are equivocal. Women compared to men, however, demonstrate a greater ability to oxidise fat and so may respond more favourably to high dietary fat intake. Previous studies employing a high fat diet are typically restricted in carbohydrate, and so a change in performance could be attributed to the manipulation of either macronutrient. The current investigation sought to determine if a high fat diet both with (HF) and without restricting carbohydrate intake (N+HF) impacts endurance performance in women compared to a control diet that reflects normal intake (N). Over three separate periods of 5 days, in a randomised counterbalanced order, women (means ± SD: age 34 ± 8 y; VO2max 55.1 ± 2.5 ml/kg/min) were provided with 3 diets designed with the following macronutrient composition (% of energy intake [carbohydrate/fat/protein]); N (50/35/15); HF (20/65/15), and a hypercaloric (130% energy intake) N+HF (50/65/15). Post-diet intervention, in the overnight fasted state, subjects completed a 90min treadmill run at 65% VO2max immediately followed by a self-paced 5km time trial (TT). Data was assessed for differences using a repeated-measures one-way ANOVA. There were no significant differences in the time taken to complete the TT (N - 1328 ± 83s; HF - 1349 ± 76s and NHF - 1333 ± 76s). Within the ranges of macronutrients provided, the total amount and proportion of dietary fat or carbohydrate consumed over five days had no impact on preloaded 5km treadmill running performance in endurance-trained women runners.